A scaled weighted variance S control chart for skewed populations - Atta, Abdu Mohammed Ali; Shoraim, Majid H. A.; Syed Yahaya, Sharipah Soaad; Zain, Zakiyah; Ali, Hazlina (2016)
This paper proposes a new S control chart for monitoring process dispersion of skewed populations. This control chart, called Scaled Weighted Variance S control chart (SWV-S) hereafter, this new SWV-S control chart is an improvement of the Weighted Variance S control chart (WV-S) proposed by Khoo et al.[11].The proposed control chart reduces to the Shewhart S control chart when the underlying distribution is symmetric.The proposed SWV-S control chart compared with the Shewhart S and WV-S control charts.An illustrative example is given to show how the proposed SWV-S control chart is constructed and works. Simulations study show that the proposed SWV-S control chart has the lower false alarm rates than the Shewhart S control chart and WV-S control chart when the underlying distributions are Weibull, lognormal and gamma. In terms of the probability of detection rates, the proposed SWV-S control chart is closer to S control chart with the exact method than those of the Shewhart S and WV-S control charts.